SARS-COV-2 Antibody Response after a Third Dose of Covid-19 Vaccine in Patients Receiving Maintenance Hemodialysis - Rabbia Rizvi, Waqar Ahmed, Mateen Akram, Abad Ur Rehman, Haris Naeem, Samee Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patients undergoing hemodialysis are at a higher risk of contracting COVID-19 infection, a virus linked to elevated mortality rates globally. By monitoring antibody levels, it is possible to evaluate the immunogenicity and potential benefits of an additional vaccine dose to guide vaccination strategies and support recommendations for a third dose to maximize protection against COVID-19 in immunocompromised dialysis patients. Objective: To evaluate the effect of the SARS-CoV-2 antibody response following a 3rd dose of the COVID-19 vaccine in patients undergoing maintenance hemodialysis. Methodology: This cross-sectional study was conducted in the Department of Nephrology at Shaikh Zayed Hospital, Lahore from 20th February 2023 to 20th August 2023. Sixty adult patients (both male and female) undergoing maintenance hemodialysis (HD), who had previously received two doses of a COVID-19 vaccine, were enrolled in the study. The humoral immune response following the second dose was assessed using the Roche Elecsys® Anti-SARS-CoV-2 S assay, which quantifies total immunoglobulin (IgG and IgM) levels directed against the spike protein (S1) of the virus. Following informed consent, a third vaccine dose was administered. The antibody response was reassessed three weeks after the third dose. Results: The mean age was 44.3±4.39 years. Majority were males 83.3%, while females accounted for 16.7%. Following the third vaccine dose, an effective antibody response was observed in 88.3% of patients, compared to 76.7% after the second dose. Conclusion: Administration of a 3rd dose of the COVID-19 vaccine significantly enhanced humoral immune response in patients receiving maintenance hemodialysis, demonstrating improved efficacy compared to the standard two-dose regimen in patients on maintenance hemodialysis. Keywords: SARS-CoV-2, COVID-19 vaccine, Hemodialysis, Humoral response, Vaccine efficacy